2022
DOI: 10.1111/j.1755-3768.2022.114
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the ultrastructural and in vitro flow properties of the PreserFlo® microShunt

Abstract: To measure the in vitro flow properties of the PRESERFLO implant for comparison with the theoretical resistance to flow. Methods:The PRESERFLO was designed to control the flow of aqueous humor according to the Hagen-Poiseuille (HP) equation. Scanning electron microscopy (SEM) was performed to analyze the ultrastructure, and flow measurements were carried out using a gravity-flow setup.Results: SEM images of the PRESERFLO showed luminal diameters of 67.73 × 65.95 μm and 63.66 × 70.54 μm. The total diameter was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In this sense, it is important to remark that the authors reported 3 out of 32 cases of surgical revision in the 0.2 mg/mL MMC group (9.3%), while in our series the percentage was higher (15.6%), due to early failure (3%) or late fibrosis (12.5%) of the filtering blebs. It is very likely that the rate of bleb fibrosis was actually comparable among their 0.2 mg/mL MMC subgroup of patients and ours, given that Preserflo provides a standardized flow rate of aqueous humor (theoretical and experimental resistance to flow=1.3 mm Hg/μL/min, pressure drop 2.6 mm Hg23), but the way in which it was managed was probably different. In fact, 1 year after surgery they reported 0.9 mean number of medications versus 0.2 in our series, suggesting a probable trend toward the use of medication instead of surgical revision for the treatment of bleb failure in their study.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…In this sense, it is important to remark that the authors reported 3 out of 32 cases of surgical revision in the 0.2 mg/mL MMC group (9.3%), while in our series the percentage was higher (15.6%), due to early failure (3%) or late fibrosis (12.5%) of the filtering blebs. It is very likely that the rate of bleb fibrosis was actually comparable among their 0.2 mg/mL MMC subgroup of patients and ours, given that Preserflo provides a standardized flow rate of aqueous humor (theoretical and experimental resistance to flow=1.3 mm Hg/μL/min, pressure drop 2.6 mm Hg23), but the way in which it was managed was probably different. In fact, 1 year after surgery they reported 0.9 mean number of medications versus 0.2 in our series, suggesting a probable trend toward the use of medication instead of surgical revision for the treatment of bleb failure in their study.…”
Section: Discussionmentioning
confidence: 67%
“…Compared with its main competitor, XEN45 (XEN-GGM; Allergan Plc, Parsippany, NJ, EEUU), most studies have reported hypotony rates comparable to PSM (Table 7), despite resistance to flow is 3.4-fold higher through XEN45. 23 Interestingly, in the study conducted by Kim et al, 29 63.2%-83.3% of the patients experienced hypotony, probably due to the high concentration of injected MMC used in the study (70% of the patients received an injection of 0.4 mg/mL without wash-out during an "ab interno"-closed conjunctiva technique). Regarding other filtering surgeries, Tables 8 and 9 show the hypotony rates reported by some studies about trabeculectomy, Express (Alcon, Fort Worth, TX, EEUU) and glaucoma drainage devices.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations